Challenging Issues and Transformation Towards Islamic Organizational Culture in A Malaysian Shariah-Based Hospital - Zaid Khaliq; Khairusy Syakirin Has-Yun Hashim (Journal of Islamic Management Studies, 2022)
The COVID-19 pandemic has indirectly affected the "wisdom" in management and the operational functions of hospitals by increasing the pressures imposed on them. According to the literature, there is a lack of implementation of Islamic hospital culture in Malaysian healthcare facilities. The objective of this research is to address issues and challenges for Islamic organizational culture in a Malaysian Shariah-based hospital, while also seeking to transform these hospital cultures and integrate them with Islamic perspectives and observations of Shariah-compliant hospitals from the past and present. This study utilizes a doctrinal analysis, which involves both primary and secondary sources of information, such as status, current healthcare practices, legal framework, and reports. The wide-ranging findings show that Shariah-based hospital are best described by their service-oriented, patient-centred culture; their distinct and unique dress standards and ambience; the availability of halal pharmaceuticals; and other features indicative of a more comprehensive approach to healthcare management based on Islamic principles. This transformation will boost up healthcare tourism for Muslims both locally and internationally by providing improved healthcare quality that is in line with Shariah practice and by making hospital more friendly to Muslims. These cultural integrations in shariah-based hospitals will open up the possibility for other interesting adaptations of Islamic organizational culture in other public services and private organizations in the future.